STRATEGI CONTEKSTUAL TEACHING AND LEARNING PADA PEMBELAJARAN FIQIH DI MADRASAH IBTIDAIYAH NEGERI 22 HULU SUNGAI TENGAH - Ubaidillah Ubaidillah (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to analyze in depth how the Implementation of Jurisprudence Learning in Using Contextual Teaching and Learning (CTL) Strategies, and how it is implemented. The type of qualitative research is descriptive analysis, research data sources are primary and secondary, data collection techniques are observation, interviews and documentation. In the technique of guaranteeing the validity of the data by data triangulation. The results of this study are the implementation of Contextual Teaching and Learning in Fiqh learning at Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah carried out in three stages, namely: first, initial activities include introduction, Second, core activities, Third, closing activities. Supporting factors are several reference books in teaching fiqh, teacher guidance in teaching, and parental guidance at home which can help the learning process outside school hours become more meaningful. The inhibiting factors are the different human resources of students, there are students who are fast in capturing understanding of the material, there are students who are slow and lagging behind in the learning process